2023
DOI: 10.1002/rmv.2427
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin for the treatment of COVID‐19 patients: A systematic review and meta‐analysis

Abstract: Currently approved therapies for COVID‐19 are mostly limited by their low availability, high costs or the requirement of parenteral administration by trained medical personnel in an in‐hospital setting. Quercetin is a cheap and easily accessible therapeutic option for COVID‐19 patients. However, it has not been evaluated in a systematic review until now. We aimed to conduct a meta‐analysis to assess the effect of quercetin on clinical outcomes in COVID‐19 patients. Various databases including PubMed, the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…However, the results did not reveal any significant differences between the quercetin and the control groups regarding CRP, ferritin, and D-dimer levels. Cheema et al in 2023 found that although quercetin did not reduce the risk of mortality or promote recovery, it did lower the rate of hospital and ICU admission (Cheema et al, 2023), which is in line with our findings regarding hospital and ICU admission.…”
Section: Discussionsupporting
confidence: 91%
“…However, the results did not reveal any significant differences between the quercetin and the control groups regarding CRP, ferritin, and D-dimer levels. Cheema et al in 2023 found that although quercetin did not reduce the risk of mortality or promote recovery, it did lower the rate of hospital and ICU admission (Cheema et al, 2023), which is in line with our findings regarding hospital and ICU admission.…”
Section: Discussionsupporting
confidence: 91%
“…Quercetin safety dose is 1000 mg/m 2 (Hollman et al 1997 ). Anti-SARS CoV-2 effects of quercetin included reduced hospitalization incidence and intensive care unit residence (Cheema et al 2023 ). Quercetin restores immune homeostasis and colonic microbiota and consolidates the intestinal barrier (Lyu et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic continues to be a global source of concern. Several therapies have been investigated for COVID-19 including oral antivirals, 1,2 repurposed medications, 3,4 and herbal supplements 5,6 but many of these have been limited by lack of evidence of substantial efficacy or high costs. Favipiravir, an oral, RNA-dependent RNA polymerase (RdRp) inhibitor, has in vitro activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
Section: Efficacy and Safety Of Favipiravir For The Treatment Of Covi...mentioning
confidence: 99%
“…Tricyclic antidepressants (mostly through H1 histaminergic blockade), maprotiline (tetracyclic), and bupropion are known to lower seizure threshold and should be avoided altogether. 5 Interestingly, SSRIs not only are a safer option (risk during FDA registration trials reported as approximately 0.2%) but also might possess an anticonvulsant activity as demonstrated in animal models but better to avoid higher doses of SSRIs because some data indicate a proconvulsant potential of SSRIs at higher doses (as the case with toxicity, overdose, or in the setting of serotonin syndrome 6 ). Another possible mechanism for antidepressantsinduced seizures is hyponatremia as part of syndrome of inappropriate secretion of antidiuretic hormone.…”
Section: Bupropion-associated Seizuresmentioning
confidence: 99%